Prediksi dan Analisis Data Gempa Bumi di Provinsi Bengkulu dengan Metode Artificial Neural Network - Fadhila Firdausa (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
Many things that have experienced technological advancements are one of which is the continued development of software. One example of software development today is the Matlab software. Matlab is currently able to be used to predict and analyze an existing problem. A lot of research has been done with the use of matlab software. Artificial Neural Network (ANN) is one of the command languages ​​used in the matlab program which is used to predict the data entered. Besides that, Bengkulu Province is one of the earthquake and tsunami prone areas in Indonesia. This is because Bengkulu is in the subduction zone (collision) of active plate encounters in Indonesia Australia and Eurasia. Recording earthquake data must be recorded properly because this earthquake data will often be used, both for development and for the environment. The ANN method uses trial epoch until the smallest error is obtained. The smallest error results stopped at the Epoch 2000 trial. The Epoch 2000 trial produced the biggest error of 59.1% and the smallest error of 2.93%. The results of this study, obtained ANN is quite capable of calculating earthquake data predictions in the province of Bengkulu in 2018.